Interactions between polyethylene and polypropylene microplastics and Spirulina sp. microalgae in aquatic systems. Issue 8 (August 2021) - Hadiyanto, H.; Khoironi, Adian; Dianratri, Inggar; Suherman, Suherman; Muhammad, Fuad; Vaidyanathan, Seetharaman
Abstract: This study aimed to evaluate the effect of microplastics on Spirulina sp., the pigment phycocyanin in Spirulina sp., and the effect of Spirulina sp. on the degradation of PE and PP plastic. The interaction of Spirulina sp. with microplstic (PE and PP) was conducted by adding the microplastic (500 mg/500 mL, with a size of 0.5–1 mm 2 ) to microalgae culture. The optical density was measured for 30 days to determine the growth of Spirulina sp. Harvesting was performed to obtain dry Spirulina sp biomass. Phycocyanin was obtained through extraction by mixing 0.1 g dry Spirulina sp. biomass with 25 ml of 1% CaCl2 in an ultrasonic water bath at 50 kHz, 300 W at 30 °C for 15 min. The results showed that the growth rate of Spirulina sp significantly decreased (p < 0.05) with treatment of PE (SP + PE) (0.0228/day) and PP (Sp + PP) (0.0221/day), compared to the control (Sp-Control) (0.0312/day). Scanning electron microscopy and Fourier transform infrared spectroscopy (FTIR) analyses of Spirulina sp. biomass with the addition of PE and PP revealed surface damage of Spirulina sp. cells and loss of carboxyl groups from proteins in Spirulina sp. at wavelengths of 1397–1450 cm −1 . In addition, Spirulina sp. had decreased the intensity of amine and amide groups from proteins at wavelengths of 3280, 1637, and 1537 cm −1 in the microplastic treatment. The phycocyanin yield and protein content in Spirulina sp. control were 19.69% and 0.147%, respectively, which decreased by 10.7% and 0.121%, respectively, with PE treatment and by 8.7% and 0.108%, respectively, with PP treatment. Moreover, the investigation of PE and PP treated by Spirulina sp showed more significant changes of functional group indicated by the formation of hydroxyl (3286 cm −1 ), carbonyl (1700 cm −1 ), ester (1750 cm −1 ) and primary alcohol (1085 cm −1 ). The results of the EDX microplastic analysis showed a decrease in carbon in PE (1.62%) and PP (1.08%). These FTIR and EDX analysis also proved that microplastic has experienced degradation when treated by Spirulina sp cell culture. Abstract : Degradation, Microplastics, polyethylene, polypropylene, Spirulina sp., Phycocyanin.